2013
DOI: 10.1007/s15010-013-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous bacterial peritonitis by Pasteurella multocida under treatment with rifaximin

Abstract: Spontaneous bacterial peritonitis (SBP) is a life-threatening complication of liver cirrhosis. Recently, rifaximin, a non-absorbable antibiotic which is used to prevent recurrent hepatic encephalopathy, has been proposed as effective prophylaxis for SBP. Here, we present an unusual case of SBP under treatment with rifaximin. A 50-year-old woman with liver cirrhosis was admitted because of tense ascites and abdominal pain. She was under long-term oral prophylaxis with rifaximin due to hepatic encephalopathy. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Lutz et al, reported a non-bite case of a patient with a cat at home. This case claimed to be the first case that occurred while a patient was taking Rifaximin for SBP prophylaxis [13] , like in our case. However, routine full susceptibility testing of Pasteurella isolates is not always needed for management, and there is no evidence that Rifaximin is effective for treatment of PM infections in humans.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Lutz et al, reported a non-bite case of a patient with a cat at home. This case claimed to be the first case that occurred while a patient was taking Rifaximin for SBP prophylaxis [13] , like in our case. However, routine full susceptibility testing of Pasteurella isolates is not always needed for management, and there is no evidence that Rifaximin is effective for treatment of PM infections in humans.…”
Section: Discussionsupporting
confidence: 62%
“…Systemic infections are rare and usually present without a recent bite [4] . Endocarditis, meningitis, and peritonitis are considered rare manifestations [4] , [8] , [12] , [13] , [14] , [15] . PM bacteremia can occur from a localized bite wound infection or from another localized source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 13 Another case suggests an alternative theory of human gastrointestinal colonization of P multocida that translocated to the peritoneal fluid to cause peritonitis. 8 However, direct testing for colonization of that patient was not performed. In addition, there are no published reports of P multocida colonization of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Of the cirrhotic cases, the outcomes have ranged from complete resolution to death. 8,9 Quite rare there are a few documented accounts of indirect exposures to animals that resulted in severe P multocida infection in patients with cirrhosis. Of those, patients presented with bacteremia, arthritis, pneumonia, or peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Au regard de sa grande diversité, il est donc fondamentale de bien la connaitre ainsi que les facteurs pouvant influencer sa composition. Malgré les importants progrès réalisés dans le domaine médical notamment dans l'efficacité de l'antibiothérapie et des techniques de réanimation, les infections intra-abdominales postopératoires restent une affection grave pour l'Homme [ 1 3 ]. Dans plusieurs études expérimentales et cliniques, il a été démontré que la sévérité de ce type d'infection était due à la présence de plusieurs espèces bactériennes qui cohabitent dans la cavité abdominale [ 4 7 ].…”
Section: Introductionunclassified